FAKTOR KONSELING DAN PENGETAHUAN YANG MEMPENGARUHI IBU POSTPARTUM DALAM MENGGUNAKAN METODE KONTRASEPSI DI KOTA KUPANG - theresia mindarsih (STIKes CHMK, 2019)
During the postpartum period mother needs counseling on the use of contraception methods. Contraceptives are needed before menstruation returns to prevent pregnancy. The purpose of this research was to know the influence postpartum counseling and mother's individual factors on use contraception methods in Kupang City. This study was quasi-experimental. 64 respondents were selected through purposive sampling and divided into 2 groups, 32 people were given counseling and 32 were not. Data collection used questionnaires. Data analysis was bivariate and multivariate. The result showed 22 respondents (68.75%) got counseling about postpartum contraception and 8 (25%) did not. The result of chi square test showed significant value of ρ = 0.000, indicating that there is influence of postpartum maternal counseling on the use of contraception methods. It is concluded that there is an influence of postpartum maternal counseling and knowledge on the use of contraception methods by mothers in Kupang City. Keywords: Counseling, postpartum, contraception use